An Analysis of Lexical Differences Between Malay and Indonesian Languages in The Film ‘Melur Untuk Firdaus’ - Kiky, Sukiyah; jafty, Jaftiyatur Rohaniyah; Dinar Vincy Yunitaka Bahrudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the lexical differences between Malay and Indonesian in the Malaysian film Melur untuk Firdaus. Although both languages ​​are derived from the same Austronesian root, variations in word meanings, forms, and external influences especially from English often lead to misinterpretation in cross-cultural communication. This study adopts a descriptive qualitative method to identify and classify vocabulary that differs in meaning between the two languages ​​and to identify Malay words influenced by English. Data were collected from 3 episodes out of 28 selected episodes using listening and note-taking techniques. Data analysis followed the interactive model of Miles, Huberman, and Saldana consisting of data reduction, data presentation, and conclusion drawing. The findings of the study revealed 34 Malay words, such as Benda, Pasal, and Lepas, that are lexically different from their Indonesian equivalents, which have the potential to cause misunderstanding. In addition, 12 English loanwords, including Busy, Telephone, and Holiday, were identified as part of code mixing, reflecting sociolinguistic and bilingual trends in Malaysian speech. These results highlight the dynamic development of language and underline the importance of understanding lexical differences to enhance shared linguistic and cultural understanding. Although limited in scope to only three episodes and lexical elements, this study provides useful insights for educators, students, and translators studying both languages.